Atmospheric Air Pollution and Monitoring - Lakhouit, Abderrahim (IntechOpen, 2020)
Indoor air quality (IAQ) is an important aspect in building design due to its effect on human health and wellbeing. Generally, people spend about 90% of their time indoors where they are exposed to chemicals, particulate matters, biological contaminants and possibly carcinogens. In particular, the air quality at hospitals carries with it risks for serious health consequences for medical staff as well as patients and visitors. This book is a study of atmospheric air pollution and presents ways we can reduce its impacts on human health. It discusses tools for measuring IAQ as well as analyzes IAQ in closed buildings. It is an important documentation of air quality and its impact on human health.